Comparing the Effectiveness of Choice Theory and Assertive Discipline Theory on the Level of Intellectual, Emotional and Behavioral Skills among High School Students - Abbas Almasi; Hasan Asadzadeh-Dahraei; Faezeh Jahan; Ameneh Moazedian (Shahid Beheshti University of Medical Sciences, 2021)
Background and Objectives: Basic life skills include intellectual, emotional and behavioral skills and the choice theory and assertive discipline theory are among the methods for training skills, especially for students. The purpose of this study was to compare the effectiveness of choice theory and assertive discipline theory on the level of intellectual, emotional and behavioral skills among secondary school students. Materials and Methods: The research method was a three-group experimental design with pre-test and post-test. The statistical population consisted of high school male high school students in Tehran in the academic year of 2018-2019. They were selected from the eleventh grade by convenience sampling method and then randomly divided into three groups of 30. Data collection tool was a life skills researcher-made questionnaire. After pre-test was performed on three groups, the choice theory and assertive discipline theory were implemented for the experimental group during eight 90-minute weekly sessions. At the end of the last session, the post-test was performed but the control group did not receive any intervention. Multivariate analysis of covariance (ANCOVA) and Scheffe's post hoc test were used to analyze the data by SPSS software version 21. Results: The mean (SD) score  of students' intellectual skills increased by 3.3 (0.3) in pre-test to 4.1 (0.3) in post-test (P<0.001), emotional skills increased from 3.1 (0.4) in pre-test to 4.1 (0.2) in post-test (P<0.001) and behavioral skills increased from 3.1 (0.6) in pre-test to 4.1 (0.3) in the post-test (P<0.001) increased in the training group by the choice theory. There were no significant differences between the mean (SD) score of intellectual skills, emotional skills and behavioral skills among students in the assertive discipline and control group. Conclusion: The study showed that choice theory had a significant effect on the intellectual, emotional, and behavioral skills of secondary school students but assertive discipline theory wasn't effective on students' basic life skills.